Synthesis and Application of Ion Selective Chelating Resin Derived from Gaur - Loonkar, Sangeeta; K. Gaur, Shiv; Daga, Kailash; Gupta, Vikal; Mishra, P. (Asian Journal of Chemistry, 2010)
Guar gum (a polysaccharide derived from the seed of guar plant, (Cyamoposis tetragonalobus) a hydrophilic polysaccharide matrix has been used for preparation of a new chelating resin. The preferential complexing tendency of different metal ions towards chelating agents anchored on a polymer has been used for separation of transition metals. The 5-amino salicylic acid group was anchored on the guar backbone in dioxane medium. This ion selective chelating resin has been used in column chromatographic separation of copper(II) and iron(III).